PERSONAL DATA AS A COMMODITY IN THE DIGITAL ECONOMY - Wardaningsih, Agustin Diana (Berumpun: International Journal of Social, Politics, and Humanities, 2025)
Personal data is a key commodity, which has led digital platforms such as Google, Facebook and TikTok to create business models that rely on the collection, analysis and use of user data to target personalized advertising. Drawing on Vincent Mosco's political economy of media theory and Dallas Smythe's concept of audience commodity, this study explores the process of commoditization of user data as the core of the digital advertising ecosystem. The study uses a qualitative approach with descriptive analysis of the digital media ecosystem, as well as case studies of digital advertising platforms that integrate predictive algorithms to maximize marketing efficiency. The findings show that personal data is not only an economic resource but also reinforces the power imbalance between digital platforms and users. Moreover, the exploitation of this data creates ethical challenges related to privacy, transparency and users' rights to their information. In conclusion, while data-driven marketing strategies offer high efficiency for advertisers, the practice demands stricter regulation to protect user privacy and prevent irresponsible data exploitation. Recommendations include increasing algorithm transparency, strengthening data regulations, and encouraging public awareness about managing their personal data in the digital age